Efficacy of integrated traditional Chinese and western medicine in managing mild-moderate acute pancreatitis: a real-world clinical perspective analysis - Jia, Sailei; Chen, Qian; Liu, Xitong; Li, Yanhong; Wang, Lihui; Li, Xian; Hu, Shixiang (Frontiers in Medicine, 2024)
Background: Given the prevalent utilization of integrated traditional Chinese and western medicine (ITCWM) in the management of acute pancreatitis, the majority of studies have concentrated on severe cases, lacking robust evidence-based medical research. Consequently, relying on real-world research, we intend to evaluate the clinical efficacy and safety of the combined approach in treating mild to moderate acute pancreatitis. Methods: A total of 563 AP patients from Henan Central Hospital were collected from January 2019 to October 2023. A propensity score matching (PSM) analysis was conducted to evaluate the clinical efficacy of traditional Chinese medicine (TCM) in treating mild to moderate acute pancreatitis. Patients were divided into a control group (61 cases) and an integrated traditional Chinese and Western medicine (ITCWM) group (120 cases). To further assess the clinical efficacy of TCM enema in the treatment of mild to moderate acute pancreatitis, PSM analysis was conducted across three groups. The patients were categorized into a control group (n=49), an oral TCM treatment group (OCM group, n=274), and an oral TCM plus enema treatment group (OCM+E group, n=131). Logistic regression was used to analyze factors after treatment in each group, and the Kaplan-Meier method compared symptom duration in each group. Results: Compared with the control group, the ITCWM group significantly decreased C-reactive protein (CRP, mg/L) (17.8[1.2-59.5] vs. 8.0[3.3-33.5], P=0.022), shortened the duration of abdominal distension, abdominal pain, nausea and bitter taste symptoms (P<0.05), and shortened the length of hospital stay (median 19.0 and 11.5 days, respectively, P=0.001); Compared with the other two groups, the neutrophil percentage (NEUT%) was lower (74.1 vs. 61.9 vs. 59.5, P<0.05) and serum prealbumin (PA, mg/L) was higher (116.0 vs. 184.4 vs. 220.0, P< 0.05), the length of hospitalization (days) was shortened (19.0 vs.12.0 vs.10.0, P<0.05) in the OCM+E group. Conclusion: The combination of traditional Chinese medicine and modern medicine has been shown to effectively decrease inflammatory indicators in patients with mild to moderate acute pancreatitis, leading to a reduction in symptom duration and hospitalization period, as well as promoting disease recovery. Notably, the use of traditional Chinese medicine in conjunction with enema therapy yields more pronounced benefits.